Characterization of sexual violence in the Guacanayabo Gulf Region of Granma Province - Beatriz María Gutiérrez Alarcón; Rafael Gutiérrez Núñez; Dielvis Alarcón Zamora; Jonathan Fonseca Roblejo (Universidad de Ciencias Médicas de Granma, 2021)
Introduction: sexual abuse or aggression constitutes a serious Public Health problem that affects with greater incidence the early ages of life. Aim: to characterize gender violence in the Guacanayabo Gulf Region. Method: a descriptive cross-sectional study was conducted in the Guacanayabo Gulf Region of the Granma province, with the cases of sexual abuse received in the Department of Legal Medicine of the Celia Sánchez Manduley Surgical Clinical Teaching Hospital. The collected data during the period of January 2015 to February 2019, was analyzed with the statistical program SPSS v.21. Results: the female sex was the most represented, with a predominance of 87.16 %. The years of 2015 and 2018 registered the highest number of cases with 25.93 and 26.20 % respectively. The age group of 8 to 15 years reported the highest number of sexually abused, with 56.83 %. Lewd abuse accounted for the highest number of cases (259), followed by rape (86). Conclusions: sexual violence in the Guacanayabo Gulf Region most frequently affects the female sex and the municipality of Manzanillo. The greatest number of sexual abuses are registered between the ages of 8 and 15 years. Lewd abuse and rape are the types of sexual abuse that predominate in female victims between 8 and 15 years of age.